Research and development activity to serve innovations in enterprises of processing and manufacturing sectors in Vietnam - Luat, Ho Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Research and Development activities (R&D) in enterprises are novel for practice in Vietnam, particularly when they are viewed in the chain of innovative activities by enterprises. The notions on innovations and R&D activities in enterprises set the theoretical background for research of R&D activities to serve innovation in enterprises. From outcomes of statistical surveys of innovations in about 8,000 enterprises in processing and manufacturing sectors in 44 provinces and central controlled cities, the paper focuses on analysis and evaluation of R&D activities in those enterprises which undertake innovations in processing and manufacturing sectors in Vietnam during 2014-2016 period. Concrete works of analysis and evaluation of R&D activities for innovations in enterprises turn focused attentions to the status of R&D units of enterprises and the number of staffs directly involved into these activities as by 31st December 2016, total expenditures for technological innovation by 2016, implementation of S&T tasks (programs and projects), applications of technical advances and solutions. Code: 19030501